Untersuchung von charakteristischen Versetzungsstrukturen und Versetzungstransportprozessen in Reibkontakten mit Versetzungsdynamik-Simulationen - Gagel, Johanna (KIT Scientific Publishing, 2019)
Plastic deformation influences the properties of tribological contacts. Therefore, it is important to understand the underlying dislocation mechanisms in tribological contacts. This work focuses on the formation mechanism of prismatic dislocation structures below an asperity and dislocation transport during sliding. Three dimensional Discrete Dislocation Dynamics simulations are conducted for a cubic face centered metal.